Level of uric acid and its, relationship with lipid peroxidation in sera of patients with acute coronary syndrome (Baghdad Science Journal, 2025)
Unstable angina pectoris often leads to acute myocardial infarction. Since uric acid is thought to be risk factor for cardiovascular disease and considered a major antioxidant in human blood .The level of uric acid and lipid peroxidation in the sera of patients with unstable angina and myocardial infarction were measured and compared to the healthy individuals. Twenty-nine patients with unstable angina and twenty-nine patients with myocardial infarction were studied and compared to twenty-five healthy individuals. Uric acid was measured by using Human Kit. Malondialdelyde (MDA) a lipid peroxidation marker, was measured by thiobarbituric acid method .Significant elevation of uric acid and MDA were observed in the sera of patients with unstable angina and myocardial infarction compared to the control group , while a non significant correlation between uric acid and lipid peroxidation were found in the present study in the sera of patients with unstable angina and myocardial infarction.